Augmented Marked Graphs - Cheung, King Sing (Springer International Publishing : Imprint: Springer, 2014)
Petri nets are a formal and theoretically rich model for the modelling and analysis of systems. A subclass of Petri nets, augmented marked graphs possess a structure that is especially desirable for the modelling and analysis of systems with concurrent processes and shared resources. This monograph consists of three parts: Part I provides the conceptual background for readers who have no prior knowledge on Petri nets; Part II elaborates the theory of augmented marked graphs; finally, Part III discusses the application to system integration. The book is suitable as a first self-contained volume on augmented marked graphs, and will be useful to both researchers and practitioners in the fields of Petri nets and system integration.